Cardiac Involvement in Systemic Sclerosis: Diagnostic Tools and Evaluation Methods. Issue 2 (March 2019) - Smolenska, Zaneta; Barraclough, Rufus; Dorniak, Karolina; Szarmach, Arkadiusz; Zdrojewski, Zbigniew
Abstract : The heart is one of the major organs commonly involved in systemic sclerosis (SSc). Myocardial fibrosis has been identified in a high percentage of these patients. Most SSc patients with cardiac involvement (CI) are subclinical, especially early on in the course of their disease. To accurately identify CI and improve diagnosis and treatment, imaging techniques should be implemented on a regular basis following diagnosis. In this review, we discuss the up-to-date pathophysiologic basis of CI, the cardiac manifestations, and the diagnostic methods that have been published in the literature. Recent studies have shown that tissue Doppler imaging is a promising evaluation technique in the bedside detection of CI. Cardiovascular magnetic resonance is an operator-independent method used for detecting SSc CI. It is an especially useful tool in the early stages of the disease when patients may be asymptomatic. At present, it is the most promising imaging technique for the diagnosis, follow-up, and response to therapy in clinical practice.